Pengembangan Sistem Tracking Lokasi Low Power Sleep Pada Wearable Device - Rioadam Sayyid Abidin; Dahnial Syauqy; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Currently, criminal rate in the world is increasing because the difficulty of getting work. One of the highest criminal case which we often heard is the case of people abduction or the case of missing people. To reduce this problem, I created a low power location tracking in wearable device for people, location tracking system is designed as small as possible so this device could be carried by the person while they're going. This system used U-Blox Neo 6M, SIM 800L, Arduino NANO, and a power bank. U-Blox Neo 6M used for the location tracking with GPS network, SIM 800L used to deliver coordinates to the tracker via SMS with GPRS network, Arduino Nano used to configure input process and output process from the system, and power bank as the primary resource which the system used. This system is filled with sleep power mode feature that became the method for the system manufacture which functioned to save the usage of the power when the system is working. Tracker could know the position of the user by writing down a predetermined keyword via SMS to the number that used by system. With this sleep power method expected to be capable of having a longer power usage and capable of reducing the case of missing people.